KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR DENGAN MENERAPKAN PENDEKATAN SANTIFIK PADA MATERI LAJU REAKSI - Manu, Frafilius Don Bosko; Hayon, Vinsensia H.B; Boelan, Erly Grizca (Jurnal Suluh Pendidikan, 2025)
This study aims to analyse students' critical thinking skills and learning outcomes after applying a scientific approach to reaction rate material. The study used a quantitative descriptive method with a one-shot case study design on 16 students in class XI IPA at Taruna Mandiri Fatubenao High School. Data were collected through critical thinking ability tests, knowledge assessments (including assignments and tests), and skill assessments (including psychomotor skills, presentations, and portfolios). The results showed that students' critical thinking skills were classified as fairly good with an average score of 46. Meanwhile, the overall learning outcomes of the students were declared complete with an average score of 84. The learning outcomes for the knowledge aspect (KI-3) obtained an average of 83, and the skills aspect (KI-4) obtained an average of 86. Although critical thinking skills were not optimal due to limited implementation time, the application of the scientific approach proved to be effective in achieving learning outcomes in both knowledge and skills aspects. This study concludes that the scientific approach can be an effective learning strategy for improving critical thinking skills and student learning outcomes in reaction rate materials.